2021
DOI: 10.1177/13540688211003304
|View full text |Cite
|
Sign up to set email alerts
|

Populist attitudes and conspiratorial thinking

Abstract: What happens to the anti-establishment sentiments of pro-incumbent voters for a populist force that is in government and thus controls the political system? This article examines this question utilizing the case of Turkey, a country in which a populist force has been in power for more than a decade. By analyzing populist attitudes among a nationally representative sample, we demonstrate that while the voters of the incumbent populist party (AKP) are less likely, compared to everyone else, to hold populist sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 78 publications
3
25
0
1
Order By: Relevance
“…Going beyond populist demonization, he now resorted more widely to the authoritarian strategy of criminalizing opponents, increasingly presenting opposition politicians and activists as terrorists or as being associated with terrorists. In line with this, Balta et al (2021) demonstrate that, compared to other voters in Turkey, AKP voters are less likely to hold populist sentiments but are more likely to endorse conspiracy theories that are about "malign foreign forces. "…”
Section: A) Ideologysupporting
confidence: 56%
See 1 more Smart Citation
“…Going beyond populist demonization, he now resorted more widely to the authoritarian strategy of criminalizing opponents, increasingly presenting opposition politicians and activists as terrorists or as being associated with terrorists. In line with this, Balta et al (2021) demonstrate that, compared to other voters in Turkey, AKP voters are less likely to hold populist sentiments but are more likely to endorse conspiracy theories that are about "malign foreign forces. "…”
Section: A) Ideologysupporting
confidence: 56%
“…While government officials encouraged people to vaccinate, they neither made this a central policy issue, nor considered to introduce incentives or obligations to encourage it. With Erdoğan's base comprising the leaders of Turkey's anti-vaxxer movement and a disproportionate share of people inclined to believe conspiracy theories (Balta et al 2021), we can speculate that not mandating vaccines is the result of a political calculus. This is another example where government rhetoric is based on scientific principles (and supports vaccines) but political considerations take precedence in policy implementation.…”
Section: D) 2021 and Beyondmentioning
confidence: 99%
“…This antagonistic thinking can also be found in conspiracy theories where "actors join together in secret agreement to try to achieve a hidden goal" (van Prooijen and Acker, 2015). Indeed, previous research has also shown a positive relationship between conspiracy mentalities and populist attitudes (Castanho Silva et al, 2017;Balta et al, 2021;Hameleers, 2021) or political extremism (van Prooijen and Acker, 2015).…”
Section: Conspiracy Mentality and Populismmentioning
confidence: 84%
“…Empirical studies about conspiracy belief during the COVID-19 pandemic often focus on specific conspiracy myths to identify affinity towards myths or the spread of these online (e.g. Eberl et al, 2021; Balta et al, 2021), for instance, the supposed connection between COVID-19 and the 5G technology (Bruns et al, 2020), or that COVID-19 is a human-manufactured virus in terms of a bioweapon (Eberl et al, 2021; Imhoff and Lamberty, 2020). Current research further illustrates that the belief in one conspiracy myth is associated with belief in other myths––even if they are entirely fictional (Swami et al, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%